Improved wireless power pickup efficiency using CMOS synchronous rectifier with embedded shorting control. Issue 1 (6th March 2017) - Gallichan, Robert; Leung, Ho Yan (Alex); Budgett, David M.; Hu, Aiguo Patrick; McCormick, Daniel
Abstract : In this work, a shorting control (SC) scheme is integrated into a complementary metal-oxide-semiconductor (CMOS) synchronous rectifier for the output voltage regulation of a wireless power supply. The rectifier is designed to operate in a parallel tuned pickup with a 500 mW output power capability for biomedical implants. Without any additional components, the proposed SC method enables the power pickup to operate with high efficiency under variable coupling conditions while maintaining the required load power to keep the output voltage constant. Desired operating conditions are achieved with increased power transfer capability at weak magnetic coupling conditions and higher power efficiency at strong coupling. A novel derivation describes the change in efficiency with SC duty ratio. Experimental validation is completed with an original custom CMOS integrated rectifier with embedded SC. It is demonstrated that the proposed SC method can increase the overall secondary pickup power transfer efficiency by 14% as the magnetic coupling increases to the stronger end.